Chemotherapy in the Setting of Severe Liver Dysfunction in Patients with Metastatic Colorectal Cancer - Pashtoon Murtaza Kasi; Gita Thanarajasingam; Heidi D. Finnes; Jose C. Villasboas Bisneto; Joleen M. Hubbard; Axel Grothey (Case Reports in Oncological Medicine)
The liver is the dominant site of metastases for patients with metastatic colorectal cancer (mCRC). Depending on the timing of diagnosis and the biology of the disease, it is not uncommon for these patients to present with visceral crisis in the form of severe liver dysfunction. Treatment of these individuals is, however, difficult and challenging. The decision to consider chemotherapy in these dire circumstances entails consideration of numerous factors. If we were to focus on just the metabolism of the different drugs and biologic agents available to treat mCRC, both 5-fluorouracil and oxaliplatin alone or in combination with a monoclonal antibody are reasonable choices. Specifically, FOLFOX is a feasible and safe option in patients with mCRC with severe liver dysfunction. Choice of the biologic agent to add to the doublet chemotherapy could be individualized based on the RAS status and the clinical scenario. Based on the divergent experience of treating 2 cases and other prior reports, a summary of recommendations with a model in the form of a “therapeutic triad” is presented. The paper highlights the therapeutic challenges in patients with mCRC and severe liver dysfunction. The choice of chemotherapeutic agents and reports of other cases/series is also presented.